Investigating the Realism or Idealism of Iran's Legislative Criminal Policy - Vanaki, Ahmadreza; Salehi, karim; Nematollahi, Meysam (Cuestiones Políticas, 2020)
This document addresses problems and questions that arise about realism or idealism in the context of the criminal policy of the double legislature in Iran, with the aim of revealing the available skills and capacities of the laws that govern the matter. Has the Iranian lawmaker followed an idealistic criminal policy? Is realism what is necessary for a dimensional criminal policy in Iran's criminal laws? What is the solution to the transition from religious idealism to a realist perspective preserving the status quo? What is certain is that, when examining existing criminal law, criminal policy based on religious idealism and dimensional realism can be seen in terms of criminological data; from the oldest data in criminal law to the latest criminal paradigms. Methodologically, documentary research technique and legal hermeneutics were used. It is concluded that traditional theologically based laws and sharia-based oversight bodies need a new dynamism and a new ijtihad. In this study, the dimensions of the subject and the form of transcendence from idealism to realism are given while preserving religious values.